A COMPARATIVE ANALYSIS OF THE DIDACTIC POTENTIAL VARIABLE AND INFURIATING DISCIPLINES IN VOCATIONAL AND LEGAL TRAINING OF FUTURE MASTERS OF SOCIAL WORK - Anna Konygina; Margarita Konygina (Вестник Северо-Кавказского федерального университета)
The article reveals the relationship of variability and invariative training, the role of variability and infuriating disciplines in the formation of General cultural, General professional and professional competencies, defines the structure and content of the variable education, its pedagogical potential, discusses the specifics of professional legal variable of training masters of social work.